Characterization of Freeze-dried Ginger Slices with Carboxymethyl Cellulose as Potential Coating Material Prior to Osmotic Dehydration - Hissham, M.H.; Kamarudin, K.H.; Isa, M.I.N; Md Salim, N.S (Rynnye Lyan Resources, 2024)
Indexed by Scopus/MyCite